Experimental determination of the critical loci for R-23 + (n-propane or n-hexane) and R-116 + n-propane binary mixtures. (May 2017) - Williams-Wynn, Mark D.; El Abbadi, Jamal; Valtz, Alain; Kovacs, Elodie; Houriez, Céline; Naidoo, Paramespri; Coquelet, Christophe; Ramjugernath, Deresh
Highlights: Critical loci measurements for R-23 + (n-propane or n-hexane) and R-116 + n-propane. Isothermal VLE measurements for R-23 + n-propane. Critical loci correlated with a Redlich-Kister type correlation. Ungerer et al. method used to critical loci from isothermal VLE data. Classification of systems according to van Konynenburg and Scott classification system. Abstract: Isothermal VLE for the (R-23 + n-propane) system was measured using a static-analytic apparatus at temperatures between T = (293.18 and 353.15) K. The critical loci for the systems R-23 + (n-propane or n-hexane) and (R-116 + n-propane) were measured using a critical point determination apparatus. The method of Ungerer et al. was used to extrapolate the isothermal VLE data to the isothermal critical locus. These extrapolated critical loci were compared with experimental data. The Redlich-Kister type correlations were used to correlate the critical loci of the systems. A critical locus curve for the (R-23 + n-hexane) system which was calculated by the method of Heidemann and Khalil was compared with the experimental critical loci. The systems were classified according to the van Konynenburg and Scott classification system.